(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 62-67 to 65-70. The name of the fifth author has changed from US Naher to UA Naher. Cultivation of modern varieties (MV) of rice in the coastal non-saline soils of the Asian countries is increasing. Nitrogen (N) deficiency is one of the most nutritional disorders for lowland rice production in Bangladesh. N management recommendation for MV rice in the coastal non-saline soils deserves special attention. A field experiment was conducted for consecutive two years aimed to determine the effect of different nitrogen levels on the yield and nitrogen nutrition of MV rice in coastal non-saline soils of Bangladesh. The field experiment involved five nitrogen levels- 50, 100, 150, 200 and 250 kg ha-1 including one N-control in randomized complete block design. The application of 150 kg N ha-1 gave the highest yield of 6.76 t ha-1 in 2009 and 6.49 t ha?1 in 2010, respectively. Total nitrogen uptake at 150 kg N ha-1 showed 112 and 116 kg ha-1 in 2009 and 2010, respectively. Results averaged over two years showed agronomic use efficiency and physiological use efficiency of 22 and 47 kg kg-1 with the application of 150 kg N ha-1. The apparent recovery efficiency of applied nitrogen (150 kg N ha-1) had 44 and 50% in 2009 and 2010, respectively. Bangladesh Rice j. 2015, 19(2): 65-70